"The impact of FDI and trade towards Malaysian economy" / Nurulhuda Zainal - Zainal, Nurulhuda (2006)
The aim of this research is to examine the impact of FDI and trade toward Malaysian economy. The research also examine the relationship of the variable that are use to measure the impact of FDI and trade to economic growth. The variables that use are the GDP, trade balance and FDI inflows in Malaysia. This paper covers 31 years study that taken in yearly basis data started from year 1975 to 2005 which means 31 data. The data will be tested by using multiple regression method and correlation test to measure the hypotheses of the study. According to the previous study found that the FDI and trade have a positive relationship for economic growth in the long run. It is expected that the study will also have a positive relationship between those variables. Thus will lead to positive impact to Malaysian economy.